Planning electric vertical takeoff and landing aircraft (eVTOL)-based package delivery with community noise impact considerations - Farazi, Nahid Parvez; Zou, Bo (Transportation research. Part E, Logistics and transportation review, 2024)
The rapid development of Advanced Air Mobility (AAM) in recent years suggests a promise to use electric vertical takeoff and landing aircraft (eVTOLs) for package delivery in metro areas. While eVTOL manufacturers and logistics service providers are actively developing prototype eVTOLs and exploring their potentials for moving freight, a system thinking about the suitability and ways to operate an eVTOL-based package delivery system remains scarce. A key aspect of the system thinking is the noise impact of eVTOL operations on surrounding communities. In this study, we provide an operation planning framework that aims to prepare AAM to be both economically efficient and community friendly for package delivery. We first develop a method to quantify the community noise impact of an eVTOL operation, using a “population exposure” measure which is based on the level of sound generated and accounts for both the number of people impacted and duration of the impact. Then, a bi-objective integer programming model is formulated which simultaneously optimizes total shipping cost and community noise impact of eVTOL operations. The optimization takes into consideration operational constraints including maximum distance for local delivery, latest package departure time from the warehouse, and eVTOL fleet size and carrying capacity. A tailored solution algorithm which augments non-dominated sorting genetic algorithm 2 (NSGA2) with compact solution representation, guided generation of initial population of solutions, and customized local search heuristics is devised. The model and the algorithm are implemented in a case study in the Chicago metro area. Numerical results reveal the trade-off between the minimization of shipping cost and community noise impact. Several operational insights about eVTOL-based package delivery are obtained. The computational efficiency and effectiveness of the proposed solution algorithm are also demonstrated in comparison with alternative solution methods. •Propose an operation planning framework for eVTOL-based package delivery.•Develop a method to quantify community noise impact of eVTOL operations.•Formulate a bi-objective integer program to optimize shipping cost and noise impact.•Design a solution algorithm augmenting non-dominated sorting genetic algorithm 2.•Implement integer program and algorithm in a case study in the Chicago metro area.